Overdiagnosis across medical disciplines: a scoping review. Issue 12 (27th December 2017) - Jenniskens, Kevin; de Groot, Joris A H; Reitsma, Johannes B; Moons, Karel G M; Hooft, Lotty; Naaktgeboren, Christiana A
Abstract : Objective: To provide insight into how and in what clinical fields overdiagnosis is studied and give directions for further applied and methodological research. Design: Scoping review. Data sources: Medline up to August 2017. Study selection: All English studies on humans, in which overdiagnosis was discussed as a dominant theme. Data extraction: Studies were assessed on clinical field, study aim (ie, methodological or non-methodological), article type (eg, primary study, review), the type and role of diagnostic test(s) studied and the context in which these studies discussed overdiagnosis. Results: From 4896 studies, 1851 were included for analysis. Half of all studies on overdiagnosis were performed in the field of oncology (50%). Other prevalent clinical fields included mental disorders, infectious diseases and cardiovascular diseases accounting for 9%, 8% and 6% of studies, respectively. Overdiagnosis was addressed from a methodological perspective in 20% of studies. Primary studies were the most common article type (58%). The type of diagnostic tests most commonly studied were imaging tests (32%), although these were predominantly seen in oncology and cardiovascular disease (84%). Diagnostic tests were studied in a screening setting in 43% of all studies, but as high as 75% of all oncological studies. The context in which studies addressed overdiagnosis related most frequently to its estimation, accounting for 53%. Methodology on overdiagnosis estimation and definition provided a source for extensive discussion. Other contexts of discussion included definition of disease, overdiagnosis communication, trends in increasing disease prevalence, drivers and consequences of overdiagnosis, incidental findings and genomics. Conclusions: Overdiagnosis is discussed across virtually all clinical fields and in different contexts. The variability in characteristics between studies and lack of consensus on overdiagnosis definition indicate the need for a uniform typology to improve coherence and comparability of studies on overdiagnosis.